Comparison of human platelet lysate alternatives using expired and freshly isolated platelet concentrates for adipose-derived stromal cell expansion. (3rd April 2019) - Dessels, Carla; Durandt, Chrisna; Pepper, Michael S
Abstract: Pooled human platelet lysate (pHPL) has been used to expand adipose-derived stromal cells (ASCs) and can be formulated using fresh or expired buffy coats (BCs) which are then resuspended in either plasma or an additive solution. Not much is known about the effects that expired products and additive solutions have on ASC expansion, and the need for quality control and release criteria has been expressed. This pilot study compared proliferation, cell size, morphology and immunophenotype of ASCs expanded in the different pHPL alternatives versus foetal bovine serum (FBS). Quality control criteria were assessed prior to and during the manufacture of the pHPL alternatives. ASCs were then expanded in 1%, 2.5%, 5% or 10% of the different pHPL alternatives or in 10% FBS. Cell size, morphology, cell number and immunophenotype were measured using microscopy and flow cytometry. The majority of the pHPL alternatives were within the recommended ranges for the quality control criteria. ASCs expanded in the pHPL alternatives were smaller in size, displayed a tighter spindle-shaped morphology, increased cell growth and had a similar immunophenotype (with the exception of CD34 and CD36) when compared to ASCs expanded in FBS. Here we report on the effects that expired BC products and additive solutions have on ASC expansion. When taken together, our findings indicate that all of the pHPL alternatives can be considered to be suitable replacements for FBS for ASC expansion, and that expired BC products can be used as an alternative to fresh BC products.